2022
DOI: 10.1111/ijac.14213
|View full text |Cite
|
Sign up to set email alerts
|

Alumina‐spinel castable for steel ladles: An overview

Abstract: Alumina‐spinel castable has excellent refractory properties, including high volume and thermal stability, good hot strength, and excellent resistance against corrosion, erosion, and thermal spalling. Excellent refractory properties have made it a preferred lining for steel ladles, reducing the erosion and corrosion of molten metal and slag and improving the ladle life and efficiency for decades. These castables are also significant for the replacement of chrome‐bearing refractories that cause several health ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…Sako et al demonstrated that refractories containing preformed and in situ spinels possessed better overall performance [ 13 ]. It was also pointed out that preformed and in situ spinel-containing castables had immense potential to enhance properties, such as strength, thermal shock resistance, and corrosion resistance [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sako et al demonstrated that refractories containing preformed and in situ spinels possessed better overall performance [ 13 ]. It was also pointed out that preformed and in situ spinel-containing castables had immense potential to enhance properties, such as strength, thermal shock resistance, and corrosion resistance [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…castables linings were corroded and deteriorated by slag and temperature fluctuation resulting in temperatureinduced phase transformation and thermomechanical properties changing, especially thermal spalling. [8][9][10][11][12] Aiming to improving their service life, several attempts found that slag resistance and thermal shock resistance of the castables can be greatly improved by adding graphite. [13][14][15] Unfortunately, high water demand derived from nonwettability of graphite flakes, therefore the castables containing graphite flakes were limited in the application in steel ladle lining because of their higher porosity, lower strength, and poor oxidation resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Al 2 O 3 ‐MgO castables have been widely used in steel ladle linings because of their good slag resistance, higher refractoriness, 1,2 which owing to the smaller grain sizes and more evenly distributed of in‐situ formed spinel grains derived from the reaction between MgO and Al 2 O 3 at elevated temperatures 3–7 . During steel refining processes, castables linings were corroded and deteriorated by slag and temperature fluctuation resulting in temperature‐induced phase transformation and thermomechanical properties changing, especially thermal spalling 8–12 . Aiming to improving their service life, several attempts found that slag resistance and thermal shock resistance of the castables can be greatly improved by adding graphite 13–15 .…”
Section: Introductionmentioning
confidence: 99%
“…Different types of the binder are used in a refractory castable system, like hydratable alumina, calcium aluminate cement, phosphate, colloidal silica, etc. [3,[7][8][9]. A significant extent of research and developmental work was carried out with calcium aluminate cement as a binder and suggested that 4 wt.% cement addition shows better properties in alumina-based castables [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Major application areas of this high alumina-based castable are steel ladle lining, purging plugs, Rh degasser, etc. [3]. A castable consists of aggregates, binders, fines, and property-enhancing additives [3].…”
Section: Introductionmentioning
confidence: 99%